A preliminary study on capsule-based self-healing grouting materials for grouted splice sleeve connection. (10th May 2018) - Liu, Yun-Lin; Wang, Yan-Shuai; Fang, Guohao; Alrefaei, Yazan; Dong, Biqin; Xing, Feng
Highlights: A capsule-based grouting material is conceived for crack self-healing. Less than 3% capsules imposed a marginal influence on engineering requirements. Free water is absorbed by the capsules to lower flowing property. Capsules may form weak zones in grouting materials. A pull-out test was performed to assess the healing effect. Abstract: Grouted splice sleeve connection is a crucial component in modular/prefabricated building structures. However, the reliability (e.g., crack-induced durability issues) of the grouting materials in the splice sleeve connection during their service life is hardly assessed. The external maintenance strategy is usually unimplemented. A capsule-based grouting material was considered in this paper to prolong the service life of the connection through self-healing micro-cracks induced by mechanical force (e.g., seismic and wind load). The influences of capsules on the grouting material in terms of flowing property, compressive strength and porosity were investigated in this paper. The morphological features of the capsule, as well as its status in uncracked and cracked (i.e., failed and triggered) grout matrix, were characterized by scanning electron microscope (SEM). The experimental results revealed that adding no more than 3% capsules into the grouting material can meet the engineering requirements of flowing property (i.e., more than 300 mm in the initial time and more than 260 mm at 30 min) and compressive strength (i.e., over 35, 60 and 85 MPa at 1-day, 3-day and 28-day, respectively). Excessive dosage of capsules added to the grouting materials increased the porosity of the matrix. The pores ranging from 100 nm to 500 nm were significantly influenced due to poor hydration (free water absorbed by the capsule), whereas the relatively large pores (>200 μm) formed weak zones in the matrix. The self-healing effect of the capsule on the splice sleeve connection was assessed by a preliminary pull-out test. It was found that the overall ductility of the connection system could be improved after self-healing for the crack-induced damage of the grouting materials.